2021
DOI: 10.1523/eneuro.0373-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

Food-Seeking Behavior Is Mediated by Fos-Expressing Neuronal Ensembles Formed at First Learning in Rats

Abstract: Neuronal ensembles in the infralimbic cortex (IL) develop after prolonged food selfadministration training. However, rats demonstrate evidence of learning the food selfadministration response as early as day 1, with responding quickly increasing to asymptotic levels. Since the contribution of individual brain regions to task performance shifts over the course of training, it remains unclear whether IL ensembles are gradually formed and refined over the course of extensive operant training, or if functionallyre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 43 publications
2
10
0
Order By: Relevance
“…Importantly, we show that an increase in food intake is seen only when deletion of MC4R is restricted to the ventral region of the mPFC, not when the deletion includes both prelimbic and infralimbic regions. This reinforces previous research showing that manipulation of neurons in the whole mPFC enhances food seeking behavior, but does not change food intake [20,21]. Furthermore, these results suggest that food-intake related behavior, potentially related to cognitive functions, are differentially regulated by mPFC subregions, conceptually consistent with results supporting distinct roles for mPFC subregions important for the expression of appetitive vs. aversive instrumental behaviors [16-18, 22, 23].…”
Section: Discussionsupporting
confidence: 90%
“…Importantly, we show that an increase in food intake is seen only when deletion of MC4R is restricted to the ventral region of the mPFC, not when the deletion includes both prelimbic and infralimbic regions. This reinforces previous research showing that manipulation of neurons in the whole mPFC enhances food seeking behavior, but does not change food intake [20,21]. Furthermore, these results suggest that food-intake related behavior, potentially related to cognitive functions, are differentially regulated by mPFC subregions, conceptually consistent with results supporting distinct roles for mPFC subregions important for the expression of appetitive vs. aversive instrumental behaviors [16-18, 22, 23].…”
Section: Discussionsupporting
confidence: 90%
“…These results are congruent with our previous findings that ensembles in the mPFC modulate cocaine SA (Warren et al, 2019 ; Kane et al, 2021 ). Furthermore, these findings suggest that Fos-expressing neuronal ensembles within the PL are critical for mediating reward seeking, even after a single day of motivated self-administration (Quintana-Feliciano et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…We have also shown that the mPFC more broadly houses ensembles that mediate recently acquired goal-oriented responding. For instance, using a similar acquisition paradigm we have found that the infralimbic cortex (IL) is necessary for initial food and oxycodone seeking (Quintana-Feliciano et al, 2021 ; Gobin et al, 2022 ). Our current findings expand this literature and support the hypothesis that ensembles in the mPFC and specifically in the PL are formed and become behaviorally relevant early in the learning process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whole‐brain networks are necessary to process, modulate, and execute complex behaviors like reward seeking. Several studies have implicated the medial prefrontal cortex (mPFC) in promoting drug (reviewed in [Kalivas & McFarland, 2003; Mantsch et al, 2016; Peters et al, 2009; Van den Oever et al, 2010]) and sucrose (Brebner et al, 2020; Caballero et al, 2019; Quintana‐Feliciano et al, 2021) seeking. The OFC and dorsal and ventral (PrL and IL) mPFC contain neurons that respond to sucrose cues (Moorman & Aston‐Jones, 2015; Stalnaker et al, 2006), and the number of Fos positive cells in these regions correlates with the degree of sucrose seeking (Grimm et al, 2016).…”
Section: Introductionmentioning
confidence: 99%